Acute pancreatitis - Barquet, Alberto (Cirugía del Uruguay, 1971)
On the occasion of the Fiftieth Anniversary of the foundation of the Surgical Society, the subject "acute pancreatitis" is being revisid. The different chapters are summarized. Insistence is laid on the frequency in its ethiology of bilio-pancreatic lithiasic pathology. Stress is laid on physiopathology and enzimatic phenomena, as represented by laboratory work. Present medical and surgical treatment is outlined.